Utylitaryzm - doktrynalna analiza ewolucji nurtu - Górecki, Olgierd (Annales. Etyka w Życiu Gospodarczym, 2011)
Utilitarianism as innovatory and original stream of ethical and political thought enrich philosophical discourse of last three centuries. Utilitarian thinkers pointed out that maximization of pleasure correlated with minimization of pain is correct way to create objective catalog of rules or behaviors which application resulted in formation of the highest utility, good for an individual and good for a society. From methodological point of view there are differences between utilitarian philosophers thought, such as: happiness, pleasure or utility guide to diametrical disaccord on ethical or institutional area. The present scientific analyzes of utilitarian thought represent attractive differences in interpretation of this doctrine. Despite of this utilitarianism does not include logical and intellectual strong arguments of protection individual man rights in the case of conflict with interest people at large. Thus this doctrine in eighteen and nineteen centuries match to postulate political egalitarianism, but in nowadays utilitarianism lost its strong ethical position. In the past utilitarianism was a political instrument attended to protect a majority of society from arbitrary reigning of small elite group of people. Modernly this thought legitimize coercion a will of majority even though other smaller group of citizens have different political point of view. This kind of thinking allow to objectify individual man which is only identified with instrumentality to maximization of utility. The author analyzed thought of Jeremy Bentham, John Stuart Mill and Herbert Spencer. Afterwards he compared their doctrines with science literature and presented a thesis that is basic and universal principles of utilitarianism and it could be actual rules of political ethics under condition of limitation theory of utility by appending law of inviolability natural rights of man.